Analisa Tindak Pidana Yang Tidak Dilakukan Penuntutan Ke Pengadilan (Studi Kasus Polres Ngawi) - Prastyawati, Herna; , Hartanto, SH., M.Hum (2016)
This study aims to know the factors that influence crime that was not done prosecutions and legal consequences arising if a criminal act can not be done to prosecutions. The results showed that the factors that influence a criminal offence was not done to prosecutions are legal factors, law enforcement, facilities or support facilities, community and culture. All factors related to each other tightly, since become essential in law enforcement as well as a measure of the effectiveness of law enforcement. Legal consequences caused make public views law enforcement is carried out by law enforcement officials is becoming weaker and less assertive, so most people underrate or underestimate the law and its enforcement apparatus should be able to complete a criminal case that occurred.